2014
DOI: 10.3390/cryst4040466
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Properties of Carbon Microcoils and Nanocoils

Abstract: Abstract:Various types of coiled carbon filaments have been synthesized using chemical vapor deposition and other methods. These carbon filaments exhibit unique electrical and mechanical properties due to their versatile shapes and structures. To form coiled shapes, different types of catalyst compositions and reactive gases have been explored. Generally, coiled carbon filaments are classified by coil diameter and shape (e.g., microcoil and nanocoil). In this review, coiled carbon filaments are classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…In 1953, Davis et al [22] firstly discovered the helical carbon fibers by the catalytic cracking of CO on the surface of refractory bricks. From then on, various morphologies helical carbon materials have been synthesized [23][24][25][26][27][28][29]. Compared to the ordinary flat carbon fibers, the HCMs in microscale or nanoscale process the characteristics of the low density, high specific strength, heat resistance, low thermal capacitance, and chemical stability [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In 1953, Davis et al [22] firstly discovered the helical carbon fibers by the catalytic cracking of CO on the surface of refractory bricks. From then on, various morphologies helical carbon materials have been synthesized [23][24][25][26][27][28][29]. Compared to the ordinary flat carbon fibers, the HCMs in microscale or nanoscale process the characteristics of the low density, high specific strength, heat resistance, low thermal capacitance, and chemical stability [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Chemie sessed a hollow configuration characteristic of CNTs (Figures 2C-D), with metal nanoparticles catalyzing carbon growth bidirectionally. [16] Different from the observation at 750 °C where the catalyst rapidly formed solid carbon in the initial state and then ceased formation over time, the lower reaction temperature slowed down the formation rate but enhanced the catalyst stability. As shown in Figure 3C, the initial carbon production rate decreased from 750 to 450 °C, as confirmed by the weight gain and w(C)/w(M) ratio of the spent catalyst after the reaction of 1 hour (Figures 3C-D, and S9).…”
Section: Methodsmentioning
confidence: 79%
“…The Fe species was encapsulated in the formed CNTs, which indicated that the Fe nanoparticles, initially located in the Al 2 O 3 support, detached from the support during the reaction. The encapsulation of Fe species by CNTs suggested that the CNT formation occurred from both ends (bi‐directional growth) [16] . Note that the bamboo‐like CNTs showed potential applications across a wide range of industries, including catalysis, sensors, and hydrogen storage materials due to their unique properties [17] …”
Section: Resultsmentioning
confidence: 99%
“…As the reaction temperature rose to 600 °C, both CNFs and CNTs were observed (Figure 3B), including tip‐growth and bidirectional‐growth [22] . At 750 °C, the resultant carbon structures possessed a hollow configuration characteristic of CNTs (Figures 2C–D), with metal nanoparticles catalyzing carbon growth bidirectionally [16] …”
Section: Resultsmentioning
confidence: 99%